The virtues of abandon : an anti-individualist history of the French Enlightenment - Coleman, Charly (Stanford University Press, 2014)
France in the eighteenth century glittered, but also seethed, with new goods and new ideas. In the halls of Versailles, the streets of Paris, and the soul of the Enlightenment itself, a vitriolic struggle was being waged over the question of ownership-of property, of position, even of personhood. Those who championed man's possession of material, spiritual, and existential goods faced the successive assaults of radical Christian mystics, philosophical materialists, and political revolutionaries. This book traces the aims and activities of these three seemingly disparate groups, and the current.